Dc and ac magnetic properties of thin-walled Nb cylinders with and without a row of antidots. (3rd May 2016) - Tsindlekht, M I; Genkin, V M; Felner, I; Zeides, F; Katz, N; Gazi, Š; Chromik, Š; Dobrovolskiy, O V; Sachser, R; Huth, M
Abstract: dc and ac magnetic properties of two thin-walled superconducting Nb cylinders with a rectangular cross-section are reported. Magnetization curves and the ac response were studied on as-prepared and patterned samples in magnetic fields parallel to the cylinder axis. A row of micron-sized antidots (holes) was made in the film along the cylinder axis. Avalanche-like jumps of the magnetization are observed for both samples at low temperatures for magnetic fields not only above H c 1, but in fields lower than H c 1 in the vortex-free region. The positions of the jumps are not reproducible and they change from one experiment to another, resembling vortex lattice instabilities usually observed for magnetic fields larger than H c 1 . At temperatures above 0.66 T c and 0.78 T c the magnetization curves become smooth for the patterned and the as-prepared samples, respectively. The magnetization curve of a reference planar Nb film in the parallel field geometry does not exhibit jumps in the entire range of accessible temperatures. The ac response was measured in constant and swept dc magnetic field modes. Experiment shows that ac losses at low magnetic fields in a swept field mode are smaller for the patterned sample. For both samples the shapes of the field dependences of losses and the amplitude of the third harmonic are the same in constant and swept field near H c 3 . This similarity does not exist at low fields in a swept mode.